2008
DOI: 10.1002/jez.462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prochloraz and ethinylestradiol on sexual development in Rana temporaria

Abstract: A wide range of environmental xenobiotics that mimic hormones (endocrine-disrupting chemicals) may cause alterations in sexual development or reproductive function in aquatic organisms such as amphibians when exposed during early sensitive stages. We exposed tadpoles of the Common frog, Rana temporaria, from hatch to metamorphosis, to two different endocrine disruptors, the synthetic estrogen 17 alpha-ethinylestradiol and the fungicide prochloraz. The object of the study was to assess the effects of these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Only one chemical of the five found to be inducers of T production in the cells, mifepristone, showed a similar trend in vivo (Wang et al 1994), while three of the seven inhibitors (prochloraz: Vinggaard et al 2005;Brande-Lavridsen et al 2008, ketoconazole: O'Connor et al 2002Monteiro et al 2000, genistein: Ohno et al 2003 revealed comparable trends between the results of the validation studies and previously reported in vivo data. However, five of the test chemicals demonstrated conflicting trends between the results obtained with the H295R cells and those from in vivo studies: the inducers atrazine (Wetzel et al 1994;Spano et al 2004) and trilostane (Jungmann et al 1983), the inhibitors letrozole (Kumru et al 2007) and aminoglutethimide (Berman and Laskey 1993;Monteiro et al 2000), and (Yamasaki et al 2002).…”
Section: Predictive Power and Accuracy Of H295r Steroidogenesis Assaysupporting
confidence: 86%
“…Only one chemical of the five found to be inducers of T production in the cells, mifepristone, showed a similar trend in vivo (Wang et al 1994), while three of the seven inhibitors (prochloraz: Vinggaard et al 2005;Brande-Lavridsen et al 2008, ketoconazole: O'Connor et al 2002Monteiro et al 2000, genistein: Ohno et al 2003 revealed comparable trends between the results of the validation studies and previously reported in vivo data. However, five of the test chemicals demonstrated conflicting trends between the results obtained with the H295R cells and those from in vivo studies: the inducers atrazine (Wetzel et al 1994;Spano et al 2004) and trilostane (Jungmann et al 1983), the inhibitors letrozole (Kumru et al 2007) and aminoglutethimide (Berman and Laskey 1993;Monteiro et al 2000), and (Yamasaki et al 2002).…”
Section: Predictive Power and Accuracy Of H295r Steroidogenesis Assaysupporting
confidence: 86%
“…While sex determination system in Rana temporaria is poorly known, it has been shown that environmental factors, such as temperature or hormonally active compounds, can induce sex reversal during early developmental stage (Bögi et al. 2003; Brande‐Lavridsen et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge from ecological and pharmaceutical literature show that the activity of many different P450 enzymes can be affected by this group of fungicides (Egaas et al 1999;Mougin et al 1991;Johnston et al 1994;Venkatakrishnan et al 2000). The azole fungicides might interfere with other biochemical pathways also as their mechanisms of action are still not fully understood (Brande-Lavridsen et al 2008;Hassold and Backhaus 2009;Taxvig et al 2008 ). The second major group of EBI fungicides includes the piperidines and the morpholines.…”
Section: Background Aim and Scopementioning
confidence: 98%